Iron-regulated NiPS for enhanced oxygen evolution efficiency. Issue 44 (6th November 2020) - Peng, Wenfeng; Li, Junkai; Shen, Kangqi; Zheng, Lirong; Tang, Hu; Gong, Yutong; Zhou, Junshuang; Chen, Ning; Zhao, Shijing; Chen, Mingyang; Gao, Faming; Gou, Huiyang
Abstract : High-purity pyrite iron nickel monophosphosulfides (Ni1− x Fe x PS, x = 0, 0.1, 0.15, 0.2) were synthesized as efficient OER catalysts for the first time by a clean high-pressure and high-temperature (HPHT) technique. Abstract : Development of robust and highly active electrocatalysts for the oxygen evolution reaction (OER) is of significance for next-generation renewable energy storage and conversion. Herein, for the first time, we report pyrite-type iron nickel monophosphosulfide (Ni1− x Fe x PS, x = 0, 0.1, 0.15, 0.2) electrocatalysts with exceptional OER efficiency and stability under alkaline conditions. Ni0.85 Fe0.15 PS/NF exhibits a considerably low overpotential of 251 (314) mV at 10 (100) mA cm −2 with a Tafel slope of 34 mV dec −1, together with remarkable stability. Moderate Fe regulation in NiPS (Ni0.85 Fe0.15 PS) is found to stimulate the activation of high-valence-state Ni/Fe oxyhydroxides during the irreversible surface reconstructions that form disordered MOOH@M x SO y @M x PO y surfaces under OER conditions, as is established by microstructural observations, surface-sensitive X-ray photoelectron spectroscopy, Raman spectroscopy and X-ray absorption spectroscopy. DFT calculations show that the catalytic sites formed by Fe doping are more nucleophilic than the Ni sites and thus more OER active, due to a facile Fe(ii ) → Fe(iii ) oxidation state change for Fe. Meanwhile, overly stable OER surface species are not formed, as Fe in oxidation states higher than Fe(iii ) is not favorable, which leads to a lower barrier for the rate-limiting OER step than that for the Ni site. The present results shed light on the design and development of high-performance electrocatalysts in ternary metal monophosphosulfides, as well as providing a fundamental understanding of their intrinsic active sites.